Flame-retardant yarn and preparation method thereof

By modifying the combination of molybdenum disulfide nanosheets and metal hydroxides with polyamide, the problem of poor flame retardant performance of polyamide materials is solved, the mechanical properties and antibacterial properties are improved, and the dense carbon layer and stable carbonization layer are significantly improved. Improves flame retardant effect.

CN119243359APending Publication Date: 2025-01-03TAIXINDA CHEMICAL FIBER (YANCHENG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229139.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The poor flame retardant properties of polyamide materials lead to limitations in practical applications. At the same time, the difficulty of compatibility between functional components and chemical fiber main body leads to uneven distribution, affecting the mechanical properties.

Method used

Modified molybdenum disulfide nanosheets and metal hydroxide mixed with polyamide, modified molybdenum disulfide nanosheets were prepared by ultrasonic reaction and lithium ion intercalation method, and spinned during the extrusion and melting process to form flame retardant yarns . Modified molybdenum disulfide nanosheets improve dispersion and compatibility through amino acid treatment, and metal hydroxide decomposes at high temperature to generate water vapor to form a stable carbonized layer, enhancing the flame retardant effect.

Benefits of technology

It improves the flame retardant properties of polyamide, enhances the mechanical properties and antibacterial properties of the material, and has light resistance and water resistance, forming a dense carbon layer and a stable carbonization layer, which significantly improves the flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025568870000061
    Figure BDA0005025568870000061
Patent Text Reader

Abstract

The invention discloses a flame-retardant yarn and a preparation method thereof, and belongs to the technical field of textiles. The flame-retardant yarn comprises the following components in parts by weight: 100 parts of polyamide, 5-15 parts of modified molybdenum disulfide nanosheets and 3-5 parts of metal hydroxides. The modified molybdenum disulfide nanosheet adopted by the invention not only has the flame-retardant and antibacterial effects of the molybdenum disulfide nanosheet, but also improves the dispersity and enhances the compatibility with polyamide after modification, and meanwhile, the modified group can also play a flame-retardant effect and play a synergistic flame-retardant effect with metal hydroxide; and the prepared flame-retardant yarn also has good water resistance. A series of performance tests prove that the flame-retardant yarn has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textiles, and particularly relates to a flame retardant yarn and a preparation method thereof. Background Art

[0002] Most common textiles are flammable. In order to prevent them from being ignited and causing fire accidents, flame retardant treatment is an effective measure. While improving the flame retardant properties of textiles, giving fabrics multifunctional integration such as hydrophobicity, antistatic, antibacterial, UV protection, and electromagnetic interference protection is an important direction for future research. Polyamide has become the most widely used type of engineering material due to its excellent mechanical properties, wear resistance, heat resistance, and easy processing and molding. However, its flame retardant properties are extremely poor, which is subject to certain limitations in practical applications.

[0003] The patent application with publication number CN 117802658 A discloses a method for preparing antibacterial flame-retardant yarn: PA6 pellets and masterbatch are mixed evenly in proportion, and the yarn is prepared by melting, extrusion oiling, pre-knotting, drafting, puffing, knotting and winding. The melting point of the masterbatch used is higher than that of the PA6 pellets but lower than the temperature of the screw extruder. The softened masterbatch can be stably dispersed in the melt, so that the functional substance is evenly dispersed in the nylon melt in the form of point-like dispersion. After spinning, the fiber has high uniformity, few stress concentration points, and limited decrease in the mechanical properties of the functional fiber. However, the functional component is usually a small molecule solid agent, which has a certain compatibility difficulty with the main body of the chemical fiber, resulting in uneven distribution of the functional component in the chemical fiber, which cannot play a corresponding effect and also reduces the mechanical properties of the chemical fiber. Summary of the invention

[0004] The object of the present invention is to provide a flame retardant yarn and a preparation method thereof, so as to improve the flame retardant property of polyamide.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A flame retardant yarn comprises, by weight, 100 parts of polyamide, 5 to 15 parts of modified molybdenum disulfide nanosheets and 3 to 5 parts of metal hydroxide.

[0007] Furthermore, the polyamide is one of polyamide 6 and polyamide 66.

[0008] Furthermore, the modified molybdenum disulfide nanosheets are prepared by the following steps:

[0009] The modifier and molybdenum disulfide nanosheets are added into acetone, subjected to ultrasonic reaction, centrifuged, filtered and washed to obtain modified molybdenum disulfide nanosheets.

[0010] Furthermore, the molybdenum disulfide nanosheets are prepared by a lithium ion intercalation method, and the specific steps are as follows:

[0011] Molybdenum disulfide powder and 1.6M hexane solution of n-butyl lithium were mixed, poured into a reactor and reacted at 110-120°C for 4-4.5 hours; after cooling to room temperature, poured into a three-necked flask, introduced nitrogen and stirred for 45-48 hours; after the reaction was completed, crude molybdenum disulfide nanosheets were filtered out, vacuum dried at 55-60°C for 4-4.5 hours, the crude molybdenum disulfide nanosheets were dispersed in deionized water and ultrasonicated for 22-24 hours, and then freeze-dried to obtain exfoliated molybdenum disulfide nanosheets.

[0012] Furthermore, the usage ratio of the molybdenum disulfide powder and the n-hexane solution is 1-1.2 g: 30-35 mL; the usage ratio of the crude molybdenum disulfide nanosheets and deionized water is 1-1.2 g: 20-25 mL.

[0013] Furthermore, the dosage ratio of the modifier, molybdenum disulfide nanosheets and acetone is 0.5-0.7 g: 5-6 g: 50-60 mL, and the ultrasonic reaction time is 22-24 h.

[0014] Furthermore, the modifier is one of 3-amino-5-mercapto-1,2,4-triazole, mercaptoethylamine and cysteine.

[0015] Furthermore, the metal hydroxide is one of aluminum hydroxide and magnesium hydroxide.

[0016] A method for preparing a flame retardant yarn comprises the following steps:

[0017] The polyamide, modified molybdenum disulfide nanosheets and metal hydroxide are uniformly mixed, extruded and melted, and spun to obtain the flame-retardant yarn.

[0018] Furthermore, during the extrusion melting process, screw temperatures T1-T8 are set to 230°C, 235°C, 245°C, 255°C, 260°C, 260°C, 245°C, and 235°C.

[0019] Beneficial effects of the present invention:

[0020] (1) The modified molybdenum disulfide nanosheets used in the present invention have a unique lamellar structure and can effectively reduce heat conduction when used as a flame retardant. At the same time, the molybdenum element is a good carbonizing agent, which can promote the formation of a dense carbon layer when the substrate burns. On the other hand, the molybdenum disulfide nanosheets have good antibacterial effects, and the lamellar structure can effectively cut the cell membrane of bacteria. The good photothermal conversion ability under light gives the material light resistance.

[0021] After the molybdenum disulfide nanosheets are modified by amino, the dispersibility of molybdenum disulfide is improved; at the same time, the amino group forms hydrogen bonds with the amide bonds, which enhances the compatibility between molybdenum disulfide and polyamide and improves the overall mechanical properties of the material; uniform dispersion also means that small molecules are not easy to fall off after washing with water, and it has the advantage of good water resistance; on the other hand, the amino group, as a flame retardant group, produces ammonia after thermal decomposition, which reduces the surrounding oxygen concentration and achieves a flame retardant effect.

[0022] (2) The metal hydroxide used in the present invention as a flame retardant has the advantages of being non-toxic, uniformly dispersed and having good water resistance. The metal hydroxide can also form hydrogen bonds with amino groups, thereby improving compatibility with other components and reducing agglomeration. In addition, the metal hydroxide decomposes at high temperatures to produce water vapor and refractory metal oxides, which form a more stable carbonized layer with the amino molybdenum disulfide nanosheets, playing a role in cooling and isolating oxygen, further improving the flame retardant effect. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment provides a flame retardant yarn, which is prepared by the following steps:

[0026] (1) 1 g of molybdenum disulfide powder and 30 mL of 1.6 M n-butyl lithium hexane solution were mixed, poured into a reactor and reacted at 120° C. for 4 h; after cooling to room temperature, poured into a 250 mL three-necked flask, introduced nitrogen and stirred for 48 h; after the reaction was completed, crude molybdenum disulfide nanosheets were filtered out, vacuum dried at 60° C. for 4 h, 1 g of crude molybdenum disulfide nanosheets were dispersed in 20 mL of deionized water and ultrasonicated for 24 h, and freeze-dried to obtain exfoliated molybdenum disulfide nanosheets.

[0027] 0.5 g of 3-amino-5-mercapto-1,2,4-triazole and 5 g of molybdenum disulfide nanosheets were added to 50 mL of acetone, ultrasonically reacted for 24 h, centrifuged at 12000 rpm for 10 min, filtered and washed to obtain modified molybdenum disulfide nanosheets.

[0028] (2) 100 parts of polyamide 6, 6 parts of modified molybdenum disulfide nanosheets and 4 parts of aluminum hydroxide were added into a high-speed mixer for mixing, extruded and melted at 260° C., and spun to obtain flame-retardant yarn.

[0029] Example 2

[0030] The present embodiment differs from the embodiment 1 in that “polyamide 6” is replaced with “polyamide 66”.

[0031] The remaining raw materials and preparation process remain the same as in Example 1.

[0032] Example 3

[0033] The present embodiment is different from the embodiment 1 in that "3-amino-5-mercapto-1,2,4-triazole" is replaced by "cysteine".

[0034] The remaining raw materials and preparation process remain the same as in Example 1.

[0035] Example 4

[0036] The difference between this embodiment and embodiment 1 is that "aluminum hydroxide" is replaced by "magnesium hydroxide".

[0037] The remaining raw materials and preparation process remain the same as in Example 1.

[0038] Example 5

[0039] The present embodiment is different from the embodiment 1 in that “6 parts of modified molybdenum disulfide nanosheets” is changed to “15 parts of modified molybdenum disulfide nanosheets”.

[0040] The remaining raw materials and preparation process remain the same as in Example 1.

[0041] Comparative Example 1

[0042] Compared with Example 1, the difference between this comparative example and Example 1 is that "ultrasound for 24 hours" in step (1) is changed to "ultrasound for 12 hours", and the specific operation steps are as follows:

[0043] (1) 1 g of molybdenum disulfide powder and 30 mL of 1.6 M n-butyl lithium hexane solution were mixed, poured into a reactor and reacted at 120° C. for 4 h; after cooling to room temperature, poured into a 250 mL three-necked flask, introduced nitrogen and stirred for 48 h; after the reaction was completed, crude molybdenum disulfide nanosheets were filtered out, vacuum dried at 60° C. for 4 h, 1 g of crude molybdenum disulfide nanosheets were dispersed in 15 mL of deionized water and ultrasonicated for 24 h, and freeze-dried to obtain exfoliated molybdenum disulfide nanosheets.

[0044] 0.5 g of 3-amino-5-mercapto-1,2,4-triazole and 5 g of molybdenum disulfide nanosheets were added to 50 mL of acetone, ultrasonically reacted for 12 h, centrifuged at 12000 rpm for 10 min, filtered and washed to obtain modified molybdenum disulfide nanosheets.

[0045] The remaining raw materials and preparation process remain the same as in Example 1.

[0046] Comparative Example 2

[0047] This comparative example is different from Example 1 in that the modification part in step (1) is removed, and the specific operation steps are as follows:

[0048] (1) 1 g of molybdenum disulfide powder and 30 mL of 1.6 M n-butyl lithium hexane solution were mixed, poured into a reactor and reacted at 120° C. for 4 h; after cooling to room temperature, poured into a 250 mL three-necked flask, introduced nitrogen and stirred for 48 h; after the reaction was completed, crude molybdenum disulfide nanosheets were filtered out, vacuum dried at 60° C. for 4 h, 1 g of crude molybdenum disulfide nanosheets were dispersed in 15 mL of deionized water and ultrasonicated for 24 h, and freeze-dried to obtain exfoliated molybdenum disulfide nanosheets.

[0049] The remaining raw materials and preparation process remain the same as in Example 1.

[0050] Comparative Example 3

[0051] Compared with Example 1, this comparative example differs in that no modified molybdenum disulfide nanosheets are added, and the specific operation steps are as follows:

[0052] 100 parts of polyamide 6 and 4 parts of aluminum hydroxide are added into a high-speed mixer for mixing, extruded and melted at 260° C., and spun to obtain flame-retardant yarn.

[0053] The remaining raw materials and preparation process remain the same as in Example 1.

[0054] Comparative Example 4

[0055] The difference between this comparative example and Example 1 is that no aluminum hydroxide is added.

[0056] The remaining raw materials and preparation process remain the same as in Example 1.

[0057] Performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4. The breaking strength was tested according to the test method specified in GB / T20218-202; the impact strength was tested according to GB / T1043.1-2008; the flame retardant properties were tested according to GB / T 2408-2021 and GB / T2406.2-2009; and the barrier film was exposed to bacteria and exposed to ordinary light for 20 minutes according to FZ / T54035-2010, and then subjected to antibacterial test. The results are shown in Table 1:

[0058] Table 1

[0059]

[0060] It can be seen from Table 1 that compared with Example 1, Example 3 is mainly manifested in the reduction of fracture strength and impact strength; compared with Example 1, Example 5 is reduced in the overall mechanical properties of the material due to excessive addition of modified nano-modified molybdenum disulfide nanosheets.

[0061] Compared with Example 1, Comparative Example 1 is insufficiently modified due to insufficient ultrasonic time, which affects the effect of amination; Compared with Example 1, in Comparative Example 2, without modifying the molybdenum disulfide nanosheets, the dispersibility of the molybdenum disulfide nanosheets themselves decreases, and hydrogen bonds cannot be formed, resulting in reduced compatibility with polyamide, and the flame retardant performance also decreases accordingly; Compared with Example 1, the results of Comparative Example 3 show that the flame retardant and antibacterial effects are greatly reduced, because the molybdenum element in the modified molybdenum disulfide nanosheets can promote the formation of a dense carbon layer when the substrate burns, thereby achieving a flame retardant effect, and the molybdenum disulfide nanosheets also have a good antibacterial effect; Compared with Example 1, after not adding aluminum hydroxide, the flame retardant effect of the flame retardant yarn in Comparative Example 4 is greatly reduced, because aluminum hydroxide decomposes at high temperature to produce water vapor and form a stable carbonized layer, which has a flame retardant effect.

[0062] In summary, the present invention provides a flame-retardant yarn and a preparation method thereof. The prepared flame-retardant yarn has good mechanical properties, flame-retardant properties and antibacterial properties, and has good application prospects in the field of textile technology.

[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flame retardant yarn, characterized in that: The invention comprises, by weight, 100 parts of polyamide, 5 to 15 parts of modified molybdenum disulfide nanosheets and 3 to 5 parts of metal hydroxide.

2. A flame retardant yarn according to claim 1, characterized in that: The polyamide is one of polyamide 6 and polyamide 66.

3. The flame retardant yarn according to claim 1, characterized in that: The modified molybdenum disulfide nanosheets are prepared by the following steps: The modifier and molybdenum disulfide nanosheets are added into acetone, subjected to ultrasonic reaction, centrifuged, filtered and washed to obtain modified molybdenum disulfide nanosheets.

4. A flame retardant yarn according to claim 3, characterized in that: The molybdenum disulfide nanosheets are prepared by a lithium ion intercalation method, and the specific steps are as follows: Molybdenum disulfide powder and 1.6M hexane solution of n-butyl lithium were mixed, poured into a reactor and reacted at 110-120°C for 4-4.5 hours; after cooling to room temperature, poured into a three-necked flask, introduced nitrogen and stirred for 45-48 hours; after the reaction was completed, crude molybdenum disulfide nanosheets were filtered out, vacuum dried at 55-60°C for 4-4.5 hours, the crude molybdenum disulfide nanosheets were dispersed in deionized water and ultrasonicated for 22-24 hours, and then freeze-dried to obtain exfoliated molybdenum disulfide nanosheets.

5. The flame retardant yarn according to claim 4, characterized in that: The usage ratio of the molybdenum disulfide powder and the n-hexane solution is 1-1.2 g: 30-35 mL; the usage ratio of the crude molybdenum disulfide nanosheets and deionized water is 1-1.2 g: 20-25 mL.

6. The flame retardant yarn according to claim 3, characterized in that: The dosage ratio of the modifier, molybdenum disulfide nanosheets and acetone is 0.5-0.7 g: 5-6 g: 50-60 mL, and the ultrasonic reaction time is 22-24 h.

7. The flame retardant yarn according to claim 3, characterized in that: The modifier is one of 3-amino-5-mercapto-1,2,4-triazole, mercaptoethylamine and cysteine.

8. The flame retardant yarn according to claim 1, characterized in that: The metal hydroxide is one of aluminum hydroxide and magnesium hydroxide.

9. A method for preparing a flame retardant yarn according to any one of claims 1 to 8, characterized in that: The following steps are involved: The polyamide, modified molybdenum disulfide nanosheets and metal hydroxide are uniformly mixed, extruded and melted, and spun to obtain the flame-retardant yarn.

10. The method for preparing a flame retardant yarn according to claim 9, characterized in that: During the extrusion melting process, the screw temperatures T1~T8 are set to 230℃, 235℃, 245℃, 255℃, 260℃, 260℃, 245℃, and 235℃.